Research on the quality of passenger transportation by railway - Maskeliūnaitė, Lijana; Sivilevičius, Henrikas; Podvezko, Valentinas (Transport, 2009)
The transportation of passengers by railroads is a dynamic process because setting, wherein the process takes place, undergoes continuous changes observed at technical, technological and transportation process planning levels. Every passenger has different needs and aims and can afford different possibilities. Therefore, the conception of quality differs in each individual case. In order to be able to plan a railway trip process in a proper manner, it is important to become familiarized with passenger needs and preferences and eliminate any existing deficiencies. To this end, it is reasonable to conduct passenger surveys. The paper provides an affinity diagram of railway transportation quality factors, the elements whereof correspond to the structure of the survey questionnaire. For determining the level of the quantitative significance (weight) of indicators, there was applied the method of Analytic Hierarchy Process (AHP) developed and introduced by the American scientist T. Saaty. The scope of research work carried out by the authors covered the determination of the highest eigenvalue, the compatibility ratio, the concordance correlation coefficient, the estimated and critical value of chi‐square values (the examples of estimations are presented in the paper) as well as the classification and processing of the surveyed data on passenger questionnaire and the analysis of respondents’ opinion. The closing part of the paper presents conclusions drawn based on the findings of the survey and respective recommendations for quality improvements in passenger transportation by Lithuanian railways. First published online: 27 Oct 2010